Дизайн інтер'єру муніципального стрілецького тиру на вул. Лисенка 23а у м.Львові - Ожог, Микола Андрійович; Ozhoh, Mykola Andriiovych (Національний університет "Львівська політехніка", 2024)
Бакалаврська робота на тему «Дизайн інтер’єру муніципального стрілецького тиру на вул. Лисенка, 23А у м. Львів» присвячена створенню сучасного, функціонального та інклюзивного стрілецького простору в межах міської інфраструктури. Метою проєкту є розробка інтер’єру, що відповідатиме вимогам безпеки, ергономіки, психологічного комфорту, а також сприятиме розвитку культури поводження зі зброєю. У першому розділі проаналізовано історичні та сучасні підходи до проектування стрілецьких тирів, визначено типологію об’єктів, вимоги до інтер’єру, стилістичні тенденції та архітектурно- просторові особливості. Особливу увагу приділено українському контексту, військовим викликам та потребі у розвитку безпекової інфраструктури. Другий розділ містить аналіз вихідних даних об’єкта, його функціонального зонування, аналіз аналогів в Україні та за кордоном, результати соціологічного опитування, а також маркетингове дослідження. Запропоновано висновки щодо потреб користувачів та конкурентних переваг. У третьому розділі викладено художньо-проєктні рішення інтер’єру, описано стилістичну концепцію, вибір матеріалів, меблів, освітлення та кольорової гами. Розроблено авторську концепцію простору, який буде одночасно безпечним, технологічним та доступним. У четвертому розділі наведено економічні аспекти проєкту: обрахунок кошторису, вибір матеріалів з урахуванням довговічності, екологічності та вартості.

The bachelor’s thesis entitled “Interior Design of the Municipal Shooting Range at 23A Lysenka Street in Lviv” is dedicated to the development of a modern, inclusive, and functionally optimized interior for a multi-level shooting complex within the urban context. This project responds to contemporary social needs related to national security, civilian training, psychological rehabilitation, and the promotion of a responsible firearm safety culture. The main objective of the project is to create an interior space that meets current safety regulations, ergonomic requirements, psychological comfort standards, and accessibility criteria, while also integrating aesthetic and technological innovations into the architectural environment. The design also supports a wide user base: school students, sports shooters, veterans, civil defense instructors, and the general public. The first chapter provides a theoretical foundation by examining the evolution of shooting range design both in Ukraine and abroad. It explores typological classifications, morphological features, stylistic approaches (such as industrial minimalism), and the specific socio- political context of contemporary Ukraine. A review of local and international case studies, regulatory frameworks (e.g., ISSF, NRA), and universal design principles is included. The second chapter focuses on analytical work: a thorough study of the architectural site, spatial zoning, and the programmatic needs of the facility. It includes an evaluation of domestic and international analogs, a marketing analysis of shooting range facilities in Ukraine, and a sociological survey conducted in Lviv regarding citizens’ attitudes towards civilian firearm access, training, and safe use. The third chapter presents the artistic and functional design concept. It features custom design elements, material palettes, lighting scenarios, furniture specifications, acoustic and ventilation strategies, as well as spatial solutions for inclusive access. Special attention is given to circulation patterns, control over weapon handling zones, and intuitive wayfinding design for user safety. The fourth chapter outlines the economic feasibility of the project. It includes detailed cost estimates for construction, standard and custom equipment, interior finishing materials, and furnishings. Environmental sustainability and long-term maintenance efficiency were considered in material selection. The resulting interior concept positions the municipal shooting range not only as a sports infrastructure, but as a multifunctional civic space — a symbol of resilience, community education, and urban security culture.
Interior design of the municipal shooting range at 23a Lysenka Street in Lviv
Keywords: 6.022.03.03; стрілецький тир; інтер’єр; муніципальний простір; інклюзивність; обороноздатність; дизайн середовища; культура безпеки; shooting range; interior design; municipal facility; inclusivity; civilian defense; user-centered design; public infrastructure; psychological safety